Survival analysis of cervical cancer patients at Wangaya Hospital, Bali Province, Indonesia - Agnes Agatha Renaningtyas Itu; Putu Cintya Denny Yuliyatni (Universitas Udayana, 2023)
Background and purpose: In Indonesia, cervical cancer has the second-highest prevalence of cancer cases after breast cancer. This study aims to determine the survival rate and to explore factors that affect the survival of cervical cancer patients at Wangaya Hospital, Denpasar, Bali. Methods: This was a retrospective cohort study. The samples were 165 cervical cancer patients who started therapy at Wangaya Hospital between 2016 – 2021 and met the research criteria. The variables retrieved from medical record were age, employment status, marital status, education level, parity, stage of cancer, type of treatment, comorbidities and time to event of death. Data were analyzed using Kaplan Meier, Log-rank test, and Cox Proportional Hazard. Results: The result shows the cervical cancer survival rate during the period of study is 67.27% with the average of follow up time was 38.4 months and a mortality rate was 7.2/1000 person months (IR=0.007). From a total of 165 patients who were sampled, 54 patients died (32.73%). Based on the results of the Cox Proportional Hazard model, it was found that the factors significantly affected the death of cervical cancer patients at Wangaya Denpasar Hospital were older age (HR=1.06; 95%CI: 1.03–1.08; p<0.001), patients who were employed (HR=2.32; 95%CI: 1.24–4.33; p=0.008), at stage 1 cancer (HR=3.94; 95%CI: 1.07–14.49; p=0.039), stage 2 (HR=5.86; 95%CI: 1.50–22.78; p=0.011), stage 3 (HR=11.73; 95%CI: 3.15-43.56; p<0.001), stage 4 (HR=18.95; 95%CI: 4.33-82.91; p<0.001) and had comorbidities (HR=2.11; 95%CI: 1.12-3.99; p=0.021). Conclusion: The survival of cervical cancer patients at Wangaya Hospital is quite good and needs to be improved. To increase patient survival, appropriate treatment is needed, especially in patients who have comorbidities and older age. Screening efforts also need to be improved to find cases at earlier stages.